2001
DOI: 10.1110/ps.9601
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the amino‐terminal β‐hairpin of the Aspergillus ribotoxins on the interaction with membrances and nonspecific ribonuclease activity

Abstract: Ribotoxins are a family of potent cytotoxic proteins from Aspergillus whose members display a high sequence identity (85% for about 150 amino acid residues). The three-dimensional structures of two of these proteins, ␣-sarcin and restrictocin, are known. They interact with phospholipid bilayers, according to their ability to enter cells, and cleave a specific phosphodiester bond in the large subunit of ribosome thus inhibiting protein biosynthesis. Two nonconservative sequence changes between these proteins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…1), although residues 7-14 constitute a shorter ␤-hairpin structure. The K11L mutant of ␣-sarcin shows both decreased ability to interact with lipid bilayers and reduced cytotoxicity (32). This led to the proposal that the absence of the second minor ␤-sheet at the NH 2 -terminal of RNases U2 or T1 could explain why they are not cytotoxic (32).…”
mentioning
confidence: 99%
“…1), although residues 7-14 constitute a shorter ␤-hairpin structure. The K11L mutant of ␣-sarcin shows both decreased ability to interact with lipid bilayers and reduced cytotoxicity (32). This led to the proposal that the absence of the second minor ␤-sheet at the NH 2 -terminal of RNases U2 or T1 could explain why they are not cytotoxic (32).…”
mentioning
confidence: 99%
“…The activity of the purified proteins was assayed by using a zymogram against poly (A) in 15% (w/v) polyacrylamide gels containing 0.1% (w/v) SDS and 0.3 mg/ml of the homopolynucleotide as previously described [19,27,28,30,[36][37][38]. After electrophoresis, the gel was washed to eliminate the SDS, incubated at pH 4.5 for 1.5 h at 37 °C, and then stained with 0.2% (w/v) toluidine blue.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…This assay is also useful to detect the presence of other RNA degrading activities in the protein samples. Volumograms of these bands (based on integrating all of the pixel intensities composing the spot) were obtained with the photo documentation system UVI-Tec (Cambridge, UK) and the software facility UVIsoft UVI band Windows Application V97.04 [19,27,28,30,38]. These data were used to quantify the activity (Table 3).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Other than this hydrophobic core, mutations affecting single residues located at the N-terminal β-hairpin of α-sarcin and the Δ(7-22) variant suggested that this protein portion would also be another region involved in the interaction with cell membranes, as they display a different pattern of interaction with lipid vesicles [68,79]. Finally, loop 2 has been proposed by several authors [26,29,30,72] to be also one of the protein regions involved in the interaction with lipids but this possibility has not been directly studied yet.…”
Section: Structural Featuresmentioning
confidence: 99%
“…These experiments confirmed that α-sarcin exhibits an intrinsic and rather specific cytotoxic character when assayed against some transformed cell lines, most probably due to the presence of acidic phospholipids on the outer leaflet of the membrane [53,54,57,58]. Consequently, all α-sarcin mutants studied that displayed an altered phospholipid interaction ability, such as that one affecting the positive charge of the active site residues Arg-121 (R121Q) [46] or, again, the Δ(7-22) deletion mutant [68], showed diminished cytotoxic effects on human rhabdomyosarcoma cells [68,79]. Obviously, mutation of the catalytically essential His-137 (H137Q) rendered a non-cytotoxic variant too [52].…”
Section: Cytoxicity Against Intact Cellsmentioning
confidence: 99%